Bandrol yükümlülüğüne aykırılık suçları (Fsek M. 81) - (:unkn) unknown (My University, 2011)
Bandrol yükümlülüğüne aykırılık oluşturan suçların Fikir ve Sanat Eserleri Kanunu’nun 81’inci maddesinde ne şekilde düzenlendiği, bandrolün nasıl alınacağı, hangi makamlar tarafından verileceği, bandrol yapıştırılması zorunlu olan eserlerin neler olduğu, eser kavramından ne anlaşılması gerektiği, eserde bulunması gerekli olan unsurların neler olduğu incelenmektedir. Ayrıca maddede düzenlenen suç tipleri tek tek ele alınmış olup, bu suçların maddi unsurları, manevi unsurları ve hukuka aykırılık halleri ile suçun özel görünüş şekilleri, yapılan güncel değişikliklerle değerlendirilmiştir. Maddenin sorun teşkil eden kısımlarına vurgu yapılarak uygulamada karşılaşılan güçlükler ve çözüm önerileri de makalemizin konusu oluşturmaktadır.

It is summarized that how the violation of stamp duty crime is organized, how stamp should be received, from which authorities it should be taken, which works are neccesary to be badged, what should be understood from the concept of work and which factors should this work require, based on the article 81 of the Law on Intellectual and Artistic Works. In addition, Not only the crime types that are organized in the article have been studied individually, but also the financial and spiritual elements of these crimes, special appearance shapes within the violation of law have been evaluated with updated changes. With special emphasis on the problematical parts of the article, the difficulties experienced in the process and suggested solutions to these problems are also the subject of our paper
Crimes of violation of stamp obligation (Code on intelllectual and artıstıc works art. 81)
Keywords: Hukuk